Dietary Feeding Lycopene, Citric Acid, and Chlorella Alleviated the Neurotoxicity of Polyethylene Microplastics in African Catfish (Clarias gariepinus) - Hamed, Mohamed; Soliman, Hamdy A. M.; Eid, Zainab; Al Naggar, Yahya; Sayed, Alaa El-Din H. (Frontiers in Environmental Science, 2022)
A few studies assessed how natural products can protect fish from the neurotoxic effects of Microplastics (MPs). Therefore, the goal of this study was to look into the neurotoxicity of PE-MPs on the brain tissue of African catfish (C. gariepinus), and whether dietary feeding on Chlorella, citric acid, and lycopene could help alleviate their toxicity. Five groups of fish were used: The first group received a standard diet (control). The second group was fed 500 mg/kg PE-MP. The third group was fed PE-MP + lycopene (500 mg/kg diet). The fourth group was fed PE-MP + citric acid (30 g/kg diet). And the fifth group was fed PE-MP + Chlorella (50 g/kg diet) for 15 days. The activities of Acetylcholinesterase (Ach), Monoamine Oxidase (MAO), Aldehyde Oxidase (AO), and Nitric Oxide (NO), and the histological effect on brain tissues were then assessed. The activity of the four neurological biomarker enzymes investigated was altered significantly in fish subjected to PE-MP alone compared with the control group. For fish exposed to PE-MP with lycopene, citric acid, or Chlorella, the activities of these neurological enzymes significantly improved particularly with Chlorella compared with fish fed PE-MP individually. Histological investigations illustrated that being subjected to PE-MPs effected cellular alterations in the telencephalon, including diffuse distorted and degraded neurons, encephalomalacia, aggregated neuroglial cells (gliosis), as well as deformed and necrotic neurons, neuropil vacuolation (spongiosis), aggregated neuroglial cells (gliosis), pyknotic neurons, and shrunken Purkinje cells which were found in the cerebellum. Most histological alterations induced by exposure to PE-MP feeding were restored by dietary feeding on Chlorella, citric acid, and lycopene. Accordingly, this study recommends using citric acid, lycopene, and Chlorella as a natural remedy against MP neurotoxicity particularly with Chlorella.